2018
DOI: 10.1051/0004-6361/201732114
|View full text |Cite
|
Sign up to set email alerts
|

Atlas of new and revised high-resolution spectroscopy of six CO isotopologues in the 101–115 nm range

Abstract: Atlas of new and revised high-resolution spectroscopy of six COisotopologues in the 101-115 nm range Transition energies of the u = 0, 1, 2, and 3 to u = 0 bands of the B 1 Σ + , C 1 Σ + , and E 1 Π to X 1 Σ + states, related term values, and molecular constants ABSTRACT Our knowledge of astronomical environments containing CO depends on accurate molecular data to reproduce and interpret observed spectra. The recent and future improvements of ultraviolet space instrumentation, both in sensitivity and resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
3
9
2
Order By: Relevance
“…The updated frequency calibration described above lead to an increase of all frequencies by 0.01 cm −1 . Our analysis of the B ← − X and C ← − X absorption bands improves upon the similar experimental study of Lemaire et al [32] , also using the DESIRS beamline. This re-analysis was necessary in order that these bands are known with a precision matching our measured VIS-FT B → A and C → A line frequencies (having uncertainties down to 0.005 cm −1 ) and sufficient to resolve the local line shifts due to energy level perturbations affecting B( v ) and C(1) levels.…”
Section: Vuv-ft Spectroscopy (Soleil Synchrotron)supporting
confidence: 81%
See 2 more Smart Citations
“…The updated frequency calibration described above lead to an increase of all frequencies by 0.01 cm −1 . Our analysis of the B ← − X and C ← − X absorption bands improves upon the similar experimental study of Lemaire et al [32] , also using the DESIRS beamline. This re-analysis was necessary in order that these bands are known with a precision matching our measured VIS-FT B → A and C → A line frequencies (having uncertainties down to 0.005 cm −1 ) and sufficient to resolve the local line shifts due to energy level perturbations affecting B( v ) and C(1) levels.…”
Section: Vuv-ft Spectroscopy (Soleil Synchrotron)supporting
confidence: 81%
“…Higher-J rotational levels than previously analysed are present in the new high-temperature absorption spectra. We also find overall energy shifts for the B(0), B(1), and C(0) vibrational levels relative to Lemaire et al [32] , of -0.05, -0.05, and 0.025 cm −1 , respectively, based on an absolute frequency calibration using the Xe reference data described above and benefiting from the simultaneous self-consistent fitting of overlapping spectra covering all bands. Small irregularities in the level energy progressions of 12 C 18 O B 1 + ( v = 0, 1) and C 1 + ( v = 0) levels are indicated in Fig.…”
Section: Vuv-ft Spectroscopy (Soleil Synchrotron)mentioning
confidence: 51%
See 1 more Smart Citation
“…Now it is generally agreed that self-shielding effect is the main reason of the massive isotope fractionation observed in the above experiment and also that in the solar system, while Thiemens´ experiment does have the effect of encouraging people to include the different photoabsorption and photodissociation cross sections for different CO isotopologues in their models, which has been proved to make the modeling results in closer agreement with the experimental measurements 17,18 . Compared to the absorption line positions, accurate absolute values of photoabsorption and photodissociation cross sections are much more difficult to be measured, thus continued recent efforts are being devoted to obtain more precise values of these for all the CO isotopologues in hope of further improving the photochemical modeling 1922 .…”
Section: Introductionmentioning
confidence: 99%
“…Whole spectroscopic studies have been devoted to characterizing the molecular parameters of all CO isotopologs so that the astronomical observations can be better interpreted and to further improve the photochemical modeling (Eidelsberg & Rostas 1990;Eidelsberg et al 1991Eidelsberg et al , 1992Eidelsberg et al , 2004Eidelsberg et al , 2006Eidelsberg et al , 2012Eidelsberg et al , 2014Eidelsberg et al , 2017Eikema et al 1994;Ubachs et al 1994;Stark et al 2014;Lemaire et al 2018), but very few studies have discussed the subsequent "trapping reactions" following the VUV photodestruction process of CO (Clayton 2011;Shi et al 2017;Lyons et al 2018). Recently, Lyons et al (2018) reanalyzed the ATMOS FTS data and found that the heavy C isotope ( 13 C) is also depleted in the Sun compared with that in the Earth and other planetary objects.…”
Section: Introductionmentioning
confidence: 99%